Hubungan self-compassion dengan parenting stress pada orang tua anak berkebutuhan khusus - Wina Marma Kusumah; Christine Masada Hirashita Tobing; Mulyadi Mulyadi (Universitas Indraprasta PGRI, 2022)
involvement in caring for children with special needs is much heavier than other normal children. The ability to interpret a life's difficulties as something that happens to everyone is called self-compassion. This research is mixed methods research with explanatory sequential design. The samples taken were 110 parents from a total population of 230 parents who were determined using a purposive sampling technique with categories, parents who have children with special needs (deaf, and mentally retarded). Informants consist of parents, teachers, and students with special needs. The instruments used in this research were a questionnaire as a quantitative analysis and observations, interviews and documentation as a qualitative analysis. The results of this study indicate a significant negative relationship between self-compassion and parenting stress on parents of children with special needs.